A multi-stimuli responsive donor-acceptor Stenhouse adducts: Synthesis, aggregation-induced emission, multi-switch behavior and information storage. (November 2022) - Wang, Chen; Yan, Qing; Wang, Sheng; Cao, Derong
Abstract: A novel donor-acceptor Stenhouse adducts (DASAs) derivative (DASA-IDN ) was constructed by introducing phenanthroimidazole (PI), tetraphenylethylene (TPE), triphenylamine (TPA) moieties into the DASAs molecular system. The multi-stimuli response process, photochromic and fluorescence properties of DASA-IDN were investigated. When irradiated with visible light, the color of DASA-IDN solution fade quickly and the fluorescence lighted up rapidly. Heating under darkroom could restore it to the initial state. Moreover, solid film of DASA-IDN have been achieved and utilized for information storage. Remarkably, DASA-IDN exhibited versatile switching behavior in response to acid, base and light, turning it into an efficient multi-stimuli responsive molecule. Graphical abstract: Image 1 Highlights: A visible light triggered phenanthroimidazole-based donor-acceptor Stenhouse adduct was constructed. The reversible multi-stimuli responsive photochromic fluorescent switching was achieved. The information storage has been demonstrated by using DASA-IDN PMMA film.